The interplay of leadership dynamics and person-centred practice in nursing homes: a mixed methods systematic review - Anker-Hansen, Camilla; Olsen, Liv Berit; Grøndahl, Vigdis Abrahamsen; Leonardsen, Ann-Chatrin Linqvist; Helgesen, Ann Karin; Bååth, Carina; Halvorsrud, Liv; Restad, Gea; McCormack, Brendan; Femdal, Ingrid (Frontiers in Health Services, 2025)
BackgroundImplementing a person-centered approach in nursing homes can significantly improve patient satisfaction and care quality while also enhancing job satisfaction among healthcare staff. Leaders play a pivotal role in establishing and nurturing a culture that supports person-centered practices. While there is some empirical evidence, a more comprehensive understanding of how leaders effectively foster and sustain person-centered practices in nursing homes is needed.AimTo investigate the role of leaders in fostering person-centeredness within nursing homes.MethodsThe study is based on the PRISMA reporting guidelines. Comprehensive searches were performed in CINAHL and PubMed, with article screening and selection facilitated by Rayyan software. A convergent integrated approach from the Joanna Briggs Institute (JBI) was used to synthesize findings from both qualitative and quantitative studies.ResultsThe review included ten studies, comprising six qualitative and four quantitative studies. The results indicate that leadership in nursing homes that fosters person-centeredness involves creating and communicating a shared vision, empowering staff, and ensuring systematic and consistent approaches. Additionally, leaders must embody person-centered values through role modeling.ConclusionsThis systematic review highlights the critical role of leadership in fostering and sustaining person-centered practices in nursing homes. Leaders carry a substantial burden of responsibility. The results suggest that a shift towards a more integrated leadership approach, incorporating both distributed and person-centered leadership models, could promote a more sustainable and supportive environment for both leaders and staff, ultimately enhancing the quality of care. These insights provide valuable guidance for nursing home leaders and policymakers aiming to strengthen person-centered practice.